Coimbra e sua região no tempo de D. Sesnando - Alarcão, Jorge de (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2021)
In 1064, Ferdinand the Great conquered Coimbra from the Musulmans. The authority over the town was trusted to Sesnandus. Born in a Christian family of Coimbra or its area, the count had been educated in the Musulman court of Seville. In the time of Sesnandus, the Christian rule was not extended farther than the line of Penela and Soure, where castles were built. The relations seem to have been peaceful between Sesnandus and the emir of Badajoz, who controlled Lisbon and Santarém. An essay is made here to imagine the urban space of Coimbra and to map the villages that existed around the town.